Perencanaan Strategi Sistem Informasi Menggunakan Ward and Peppard pada PT. Priadi Sidik Jari Psikologi - Imannudin Akbar; Fikri Muhamad Fahmi (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2022)
In this era, technological advances force companies and organizations to adapt in order to compete with their competitors. Strategic planning of information systems has a major impact on the continuity of business competition. PT. Priadi Sidik Jari Psikologi is a psychological assessment institution that has used information systems to support its business activities, but the implementation has not been maximized. Therefore, to maximize the existing information system at PT. Priadi Sidik Jari Psikologi, it is necessary to strategically plan information systems to achieve the company's vision, mission and goals. In this research, the Ward and Peppard framework is used with several analysis techniques including: PESTLE, Porter's Five Competitive Forces, and Value Chain analysis to analyze the internal and external environment of the business, SWOT to analyze the internal and external environment of SI and IT, and McFarlan Strategic Grid for application portfolio mapping. The results of this research are expected to improve the company's achievements and can also be used as a reference for the development of information systems in the company.